RELAKSASI KREDIT PERBANKAN BAGI PELAKU USAHA DALAM MASA PANDEMI COVID 19 - suwardi suwardi; Indrati Rini (Fakultas Hukum Universitas Narotama, 2021)
In encouraging the business world to run well, bank institutions must be able to provide more extreme strategies, that if banks want to get out of a slump, then banks should not use old methods or ways of marketing their products and services. Corona has deconstructed the banking order/system that has been running so far the Covid-19 pandemic has forced individuals/groups/institutions/countries to change their lifestyle and behavior so far. If an individual / group / institution / country does not make changes, then the changes will automatically crush them, without exception in the banking business sector. Several business sectors have been affected by the coronavirus (Covid-19) pandemic, including the banking sector. Therefore, in order for the banking sector to continue to exist in the midst of the corona virus pandemic, banks must carry out risk mitigation carefully, and use creative strategies to deal with current uncertain conditions. Banks must immediately adapt to the conditions of the Corona virus pandemic by implementing new strategies, and returning to the path of good performance. It is hoped that the intermediary function of the bank will run smoothly and be able to leverage Indonesia's national economic growth in the new normal era Key words: relaxation, banking credit, business actors, the pandemic period